1088 Ventilation Modality and Cerebral Damage in Preterm Infants. (October 2012) - Arco, A; Pagano, GT; Gitto, E; Aversa, S; Barberi, I
Abstract : Background and Aims: Several studies on high frequency oscillatory ventilation (HFOV) have demonstrated a high relation between this method and the incidence of hemorrhagic or ischemic brain injures. In this study, we meant to verify the incidence of intra-periventricular hemorrhage (III–IV stadium) and cystic periventricular leukomalacia (CPVL) in subjects submitted to different ventilation (HFOV vs CMV). Materials and Methods: We have examined 120 newborns (mean gestational age 30±1.85 weeks, mean birth weight 1314±404.14 grams). Group A: 60 infants ventilated in HFOV; Group B: 60 infants ventilated in CMV. All received surfactant. All infants underwent monitoring of cardiovascular function with evaluation of parameters such as fractional shortening, ejection fraction, size of rooms, the ductal shunt, pulmonary artery pressure and cardiac output and blood pressure. Results: Infants ventilated in HFOV have required a maximum value of MAP significantly lower (p<0.05) versus those ventilated in CMV; Iin group A, 8 (13.3%) experienced a hemorrhage of III–IV degree against 12 (20%) of subjects in group B. They presented CPVL 14 (7.23%) infants in group A compared with 16 (26.6%) in group B. There were no differences in cerebral blood flow and resistance index of the anterior cerebral artery. There were no differences in cardiac function. Conclusions: Our data show an increase, not statistically significant, of PIVH and CPVL in newborn infants treated with conventional ventilation than oscillatory ventilation. This is attributable to the use of a MAP "optimal" able to obtain a good alveolar recruitment without causing hyperexpansion.